Quality matters: International standards for biobanking. Issue 8 (16th June 2022) - Dagher, Georges
Abstract: Human biospecimens provide the basis for research, leading to a better understanding of human disease biology and discovery of new treatments that are tailored to individual patients with cancer or other common complex diseases. The collection, processing, preservation, storage and providing access to these resources are key activities of biobanks. Biobanks must ensure proper quality of samples and data, ethical and legal compliance as well as transparent and efficient access procedures. The standards for biobanking outlined herein are intended to be implemented in biobanks and to supply researchers with high‐quality samples fitted for an intended use. Abstract : Several variables in the pre‐analytical phase can affect the quality of biological samples. © K. Zatloukal.